AeU Style Guide for Graduate Students using American Psychological Association (APA) Format - Rashidah, Alimat (AeU Knowledge Centre, 2016)
The Asia e University Style Guide aims to provide guidance on proper ways of constructing reference list for students preparing to write PhD and master theses. Examples provided are based on rules of American Psychological Association (APA) style. Graduate students are required to follow the style guide provided for consistency and good presentation style when citing sources.